Utilization of Fruit and Vegetable Processing Technology: Supporting Sustainability, Waste Reduction, and Improved Nutrition - Indriyani Indriyani; Laeli Nur Hasanah; Restu Auliani; Etty Sri Hertini; Soni Suharmono (Westscience Press, 2023)
Utilizing technologies for processing fruits and vegetables is crucial for tackling major issues with contemporary food systems. In the supply chain for fruits and vegetables, this research examines the diverse effects of processing methods on sustainability, waste reduction, and nutritional improvement. Our study employs a mixed-methods approach that combines qualitative information from expert interviews with quantitative data analysis from 150 samples to provide a thorough evaluation of this topic. The results show that processing technologies have a considerable impact on waste reduction, energy conservation, and resource efficiency. These technologies are also crucial for extending product shelf life and raising marketable yield, which decreases food waste. Although some nutrients are lost during processing, cutting-edge methods have been shown to increase nutrient retention. This study not only clarifies the intricate relationships that exist between processing technologies and sustainability, but it also offers a foundation for future research in this vital area. The lessons learned from this study have significant significance for the creation of sustainable and nutrient-dense food systems as we struggle with the urgent challenge of feeding a growing global population while protecting the environment and enhancing nutrition.